LEXICAL SEMANTIC ANALYSIS ON THE LYRICS OF NIKI’S SONG “OCEANS AND ENGINES” - Syah Putra, Aidil; Qodriyati, Nurul Lailatul; Maharani, Ika Shakila (Media Inovasi Pendidikan dan Publikasi, 2024)
The lyrics to NIKI's song